Molecular Features in Lymphatic Metastases Reflect the Metastasis Mechanism of Lymph Nodes With Non-Small-Cell Lung Cancers - Guo, Nannan; Chen, Yuanyuan; Jing, Zhongying; Liu, Siyao; Su, Junyan; Li, Ruilin; Duan, Xiaohong; Chen, Zhigong; Chen, Ping; Yin, Rongjiang; Li, Shaojun; Tang, Jian (Frontiers in Bioengineering and Biotechnology, 2022)
Lymphatic metastasis influences clinical treatment and prognosis of patients with non-small cell lung cancer (NSCLC). It is urgent to understand molecular features and mechanisms of lymph node metastasis. We analyzed the molecular features on pairs of the primary tumor and lymphatic metastasis tissue samples from 15 NSCLC patients using targeted next-generation sequencing. The potential metastasis-related genes were screened from our cohort based on cancer cell fraction. After filtering with gene functions, candidate metastasis-related events were validated in the MSK cohort with Fisher’s exact test. The molecular signature and tumor mutational burden were similar in paired samples and the average mutational concordance was 42.0%±28.9%. Its metastatic mechanism is potential a linear progression based on the metastatic seeding theory. Further, mutated ataxia telangiectasia mutated and Rad3-related (ATR) and tet methylcytosine dioxygenase 2 (TET2) genes were significantly enriched in lymphatic metastases (p ≤ 0.05). Alterations in these two genes could be considered metastasis-related driving events. Mutated ATR and TET2 might play an active role in the metastasis of lymph nodes with NSCLC. More cases enrollment and long-term follow-up will further verify the clinical significance of these two genes.